Pengembangan Modul Pembelajaran Penggunaan ArcGIS Online untuk Pembuatan Peta Penyebaran Gedung: Studi Kasus pada Peta Penyebaran SMK Kompetensi Keahlian DPIB di Daerah Istimewa Yogyakarta - Hanna Nursanti Sukmantari; Ilham Marsudi; Nuryadin Eko Raharjo (Universitas Negeri Yogyakarta, 2022)
ABSTRACTThe purpose of this study was to develop a learning module for the use of ArcGIS Online in making the distribution map of the SMK DPIB expertise program in DIY in the Geomatics Practicum II course in the Department of Civil Engineering and Planning UNY. This research is included in research and development or Research and Development (R&D), the 4D (four-D) method by Thiagarajan. The data collection technique spreads questionnaires to respondents. Qualitative descriptive technique as a data analysis technique. The results of this study are: (1) The development of learning media through the 4D stage. The defining stage (Define) is to obtain the needs in using ArcGIS Online., The selected media design stage is the learning module, the development stage (Develop) stage is validated by material experts, and media experts then a feasibility test is carried out on the user ,, and the dissemination stage (Disseminate), the dissemination stage is carried out by spreading the media that has been developed. The learning media developed is a learning module. The feasibility of the learning module is based on the assessment of the material expert, namely 3.93 with the